Potentials for savings in the Slovenian public enterprises and investments in infrastructure? - Nevenka Hrovatin (Central European Public Administration Review)
The author analyses the success rate and efficiency of Slovenian public sector companies in the course of their operations and looks into opportunities for savings and ways of attracting private investment in infrastructure. By reducing expenditures public companies achieve higher profits, from which the state in turn receives firstly, dividends as a form of budgetary revenue; and secondly, increased tax revenues, as public companies are not exempt from paying corporate income tax. By increasing the rate of return in public companies, the state therefore receives a larger slice of the budget pie on account of its two roles – as both owner and administrator, and as fiscal generator and provider. The author concludes that Slovenian companies cannot achieve identified possible savings without the efficient management of public sector companies. To this end at least two reforms should be introduced in Slovenia: firstly, the introduction of a system of contracts between the state and public sector companies on the meeting of specific pre-determined goals; and secondly, the establishment of a politically independent system of recruitment and appointment of managers based on professional references, and a management remuneration system tied to either the operating results achieved by said public companies or on the meeting of certain pre-determined goals set out in contracts between the state and public companies.